A Critical Review of the Actualization of the Right to Control by the State Doctrine in the Policy on Revocation of Forest Area Permits/Concessions - Totok Dwi Diantoro (PROGRAM STUDI MAGISTER HUKUM FAKULTAS HUKUM UNIVERSITAS DIPONEGORO, 2025)
The Right to Control by the State (Hak Menguasai Negara or HMN) is a doctrine derived from Article 33 paragraph (3) of the 1945 Constitution of the Republic of Indonesia, which asserts that the land, water, and natural resources contained therein shall be controlled by the state for the greatest benefit of the people. In its decision, the Constitutional Court explained that the phrase